Noble Metal‐Free CoSx/NiSx Heterojunction for Photo‐Assisted Methanol Electrooxidation. Issue 19 (5th October 2022) - Wang, Feng; Wu, Lisha; Qian, Lei; Li, Guanfeng; Sun, Yonghua; Zeng, Ying
Abstract: Designing noble metal‐free anode catalysts for photo‐assisted direct methanol fuels cells still remains a significant challenge. In this report, CoSx /NiSx heterojunction was prepared by a two‐step method containing room temperature coordination reaction and calcination using L‐cysteine as both organic ligands and sulfur sources. The as‐prepared CoSx /NiSx heterojunction displayed a significant enhancement in the methanol electrocatalytic oxidation activity under the light irradiation by combining their electrocatalytic and photocatalytic properties. The photocatalytic process was discussed in detail to explore the photo‐assisted enhancement mechanism. The electrochemical and photochemical results indicated that, the synergistic effect of electro‐ and photocatalytic reaction contributes to the enhanced catalytic performance. This work provides a new paradigm to improve the methanol electrocatalytic activity of noble metal‐free semiconductor catalyst. Our proposed noble metal‐free CoSx /NiSx heterojunction will have potential use in photo‐assisted direct methanol fuel cells. Abstract : Photo‐assisted methanol electrocatalytic oxidation : CoSx /NiSx heterojunction was prepared and displayed a significant enhancement in the methanol electrocatalytic oxidation activity under the light irradiation by combining their electrocatalytic and photocatalytic properties. This work provides a new paradigm to improve the methanol electrocatalytic activity of noble metal‐free semiconductor catalyst.